2021
DOI: 10.1371/journal.pone.0239021
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the effect of a scanner upgrade on measures of grey matter structure for longitudinal designs

Abstract: Longitudinal imaging studies are crucial for advancing the understanding of brain development over the lifespan. Thus, more and more studies acquire imaging data at multiple time points or with long follow-up intervals. In these studies changes to magnetic resonance imaging (MRI) scanners often become inevitable which may decrease the reliability of the MRI assessments and introduce biases. We therefore investigated the difference between MRI scanners with subsequent versions (3 Tesla Siemens Verio vs. Skyra) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…TBSS on the FA skeleton presented a pattern with higher FA values for Verio data in more superficial white matter and higher FA values for Skyra data in rather deep WM areas. We observed a bias similar to this pattern when comparing anatomical MR images from Verio and Skyra [ 65 ], namely Skyra exhibiting higher cortical thickness and larger GM volumes in medial frontal and central regions and Verio showing higher cortical thickness in lateral and occipital regions. This pattern could be caused by scaling differences between scanners that were observed on the anatomical images and could affect diffusion image processing due to registration on the individual anatomical images.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…TBSS on the FA skeleton presented a pattern with higher FA values for Verio data in more superficial white matter and higher FA values for Skyra data in rather deep WM areas. We observed a bias similar to this pattern when comparing anatomical MR images from Verio and Skyra [ 65 ], namely Skyra exhibiting higher cortical thickness and larger GM volumes in medial frontal and central regions and Verio showing higher cortical thickness in lateral and occipital regions. This pattern could be caused by scaling differences between scanners that were observed on the anatomical images and could affect diffusion image processing due to registration on the individual anatomical images.…”
Section: Discussionsupporting
confidence: 55%
“…Additionally, in a parallel comparison of the anatomical images from Verio and Skyra, gradient non-linearity correction—conducted with the gradunwarp implementation [ (accessed on 5 October 2021)] in Python 2.7. )—did not substantially reduce the detected differences [ 65 ]. This is why we estimate that gradient non-linearities might only explain a small share of the differences in the WM skeletons between the scanners.…”
Section: Discussionmentioning
confidence: 99%
“…These systematic effects may rather stem from differences in the imaging sequence used on the two sites (higher resolution in Dresden) which may have locally affected the FreeSurfer segmentation algorithm. Further, a scanner update was completed during wave three in Paris (Siemens Trio to Prisma) which may have introduced additional bias in results as Medawar et al (2021) and Plitman et al (2021) reported very good ICC but also percent volume differences in several cortical and subcortical regions when comparing Siemens Scanners (Trio versus Prisma/Verio versus Skyra). Since many recent longitudinal studies on brain development included several samples with differences in imaging sequence and scanner type (Dennison et al, 2013; Mills et al, 2021; Tamnes et al, 2017; Wierenga, Sexton, et al, 2018), results should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that even slight modification to the scanner software can result in bias in the acquired dMRI data, similar to a "site-effect," even when the acquisition protocol remains unchanged (Medawar et al 2021;Bayer et al 2022). However, it is often difficult to predict the bias in the data due to such software updates.…”
Section: Scanner-software Upgrades In Each Abcd Study Sitementioning
confidence: 99%